Typology of Coastal Traditional Houses of the Bajo Tribe in Bajoe Village, Soropia District, Southeast Sulawesi - Setiadi, Ahsan Hidayat; Wulandari, Lisa Dwi; Asikin, Damayanti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Geographically Soropia subdistrict is located in Konawe district of southeast Sulawesi province consisting of a large quantity of coastal areas that are the site of transition between land and the ocean. This condition has indirectly affected the shape of the character of this area caused by the relocation carried out by the government in an effort to build a tourist area in pualu bokori to move the coastal settlement in the village of bajoe soropia subdistrict. This coastal settlement is a form of reflection of the sea culture attached to the bajo tribe community. One of the coastal settlements in this soropia subdistrict is a settlement in the village of Bajoe which is a coastal settlement with a constructive orientation leading to land orientation. Because of the issue, in the village of Bajo and surrounding areas there are three different site orientations in coastal areas, among others, namely: water-based architecture water buildings, semi-arir buildings that tread in the water and also land and land-based architecture land buildings. Based on the issue, in this coastal area there is a diversity of typologies which is a form of morphological transformation of the shape of the bajo house. Therefore, in this study using descriptive qualitative research methods are expected to be able to find out the variety of typologies found in the coastal settlement area of the bajo tribe in bajo village soropia subdistrict konawe district. So that  the results can be  from  this  research  can be a  new  insight  literature as well as a reference  in  consideration  in the planning of future settlements.